Leveraging AI-generated and human-generated content for maximized user engagement in contentpreneurs’ innovation and creativity - M. Eshaq Stanikzai; Ella Mittal (Journal of Innovation and Entrepreneurship)
Abstract The rapid expansion of digital content has transformed engagement dynamics. Despite their growing influence, the impacts of AI-generated content (AIGC) and human-generated content (HGC) on user engagement (UE) via contentpreneurs’ innovation and creativity remain insufficiently explored. Addressing this research gap, this study examines how AIGC and HGC, via contentpreneurs’ innovation and creativity, influence UE. Using web-based and telephone survey data from 324 contentpreneurs across YouTube, Instagram, X, and Facebook, the study employs a CB-SEM approach to investigate the association between the construct variables. The findings disclose that AIGC and HGC significantly impact UE. The HGC effect is more convincing than AIGC due to its ability to foster authenticity, emotional connection, and personalized user experiences. Innovation and creativity are partial mediators, influencing the relationship between the predictors and the outcome variable. The study introduces an original conceptual model within contentpreneurship theory, integrating sustainability considerations into digital engagement strategies. It contributes to the creator economy by emphasizing the strategic value of both types of content creation in boosting innovation and creativity. This research highlights the optimization of AIGC and HGC, strategic brand building, and the sustainable development of their innovation and creativity. It also highlights the need for adaptable incentives.